Effectiveness of risk based internal auditing: a case of Central Africa Building Society (CABS) – (January 2010 - October 2013) - Mapfeka, Prince Tapiwa (2014)
This study sought to analyze the effectiveness of risk based internal auditing in the Central Africa Building Society (CABS). Literature from different authors was reviewed to analyze and evaluate different insights on the risk based internal audit policy. Descriptive research design was used to assess the effectiveness of the risk based internal audit system. The researcher used stratified random sampling to determine the population and the sample size. A sample size of 20 respondents was used for the purpose of this research. Questionnaires and interviews were used as the research instruments for primary data collection. Major research findings were presented and analyzed using the mode and percentages to depict the results. The study concluded that risk based internal audit with the adoption of enterprise risk management is the best practice to mitigate risks in the bank.